Deglutition Impairment during Dual Task in Parkinson Disease Is Associated with Cognitive Status - Ardenghi, Luciana Grolli; Signorini, Alana Verza; Maahs, Gerson Schulz; Selaimen, Fabio; Deutsch, Konrado Massing; Dornelles, Silvia; Rieder, Carlos Roberto de Mello (International Archives of Otorhinolaryngology, 2020)
Introduction Dysphagia is a relevant symptom in Parkinson disease (PD), and its pathophysiology is poorly understood. To date, researchers have not investigated the effects of combined motor tasks on swallowing. Such an assessment is of particular interest in PD, in which patients have specific difficulties while performing two movements simultaneously.Objective The present study tested the hypothesis that performing concurrent tasks could decrease the safety of swallowing in PD patients as visualized using fiberoptic endoscopic evaluation of swallowing (FEES).Methods A total of 19 patients and 19 controls matched by age, gender, and level of schooling were compared by FEES under two conditions: isolated swallowing and dual task (swallowing during non-sequential opposition of the thumb against the other fingers). The two tasks involved volumes of food of 3 mL and 5 mL. The PD subjects were classified according to the Hoehn & Yahr (H&Y) Scale, the Mini Mental State Examination (MMSE), and the Montreal Cognitive Assessment (MoCA). The FEES assessment was performed according to the Boston Residue and Clearance Scale (BRACS).Results The data showed a significant worsening of swallowing in the dual task assessment for both volumes (3 mL: p ≤ 0.001; 5 mL: p ≤ 0.001) in the PD group. A correlation between the MoCA and dual-task swallowing of 3 mL was also found.Conclusion These findings suggest that additional tasks involving manual motor movements result in swallowing impairment in patients with PD. Moreover, these data highlight the need to further evaluate such conditions during treatment and assessment of PD patients.
Keywords: deglutition disorders; Parkinson disease; endoscopy; cognition